(untitled) (Revista Brasileira de Contabilidade e Gestão, 2016)
This research aims to examine the leadership styles, the results orientation and strategic management practices of people used by financial institutions public and private. The study has cross-cutting and time is exploratory in nature. The research was based on structured questionnaires that seek to measure the Human Resources Policies (14 issues) and Leadership Characteristics (13 questions). Data were collected in March in 13 bank branches with a sample of 124 randomly chosen bank. With use of factor analysis, the 27 initial questions were summarized in three factors (dimensions): 1) Human Resources Policies; 2) Leadership: Motivation and Efficiency in results, and; 3) Leadership: Focus on Results. The results show the tendency of managers to adopt the transformed leadership, a factor that favors the employee commitment to the mission and goals of the organization. But the leadership style is results- oriented, showing suitability for business goals. Finally there was the focus of financial institutions in the compromise, portraying the satisfaction of employees with the employed people management policies. It is hoped that this research will facilitate the identification of leadership and strategic management of people both in the financial institutions, such as other organizations, since it shows that the higher investment in strategic management policies of people transform vision, and result-oriented, higher employee satisfaction.